2017
DOI: 10.3390/ijerph14030255
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Trends among U.S. Latinos, 1998–2013: The Impact of Immigrant Arrival Cohort

Abstract: Few studies examine nativity disparities in smoking in the U.S., thus a major gap remains in understanding whether immigrant Latinos’ smoking prevalence is stable, converging, or diverging, compared with U.S.-born Latinos. This study aimed to disentangle the roles of period changes, duration of U.S. residence, and immigrant arrival cohort in explaining the gap in smoking prevalence between foreign-born and U.S.-born Latinos. Using repeated cross-sectional data spanning 1998–2013 (U.S. National Health Interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…This contradiction between the relative socioeconomic disadvantage and health of Hispanics vis-a-vis whites has been labeled the Hispanic paradox ( Markides & Eschbach, 2011 ). Potential explanations for the observed health advantage among older Hispanics have been attributed to (a) selective migration: in-migration of healthy individuals and return migration of older Hispanics in poor health to their country of origin, which results in a healthier Hispanic population residing in the United States ( Bostean, 2013 ; Markides & Eschbach, 2005 ); and (b) social and cultural factors among Hispanic immigrants associated with positive health behaviors (e.g., lower levels of smoking, and healthier diet) that promote health and longevity ( Bostean, Ro, & Fleischer, 2017 ; Fenelon, 2013 ; Lariscy, Hummer, & Hayward, 2015 ; Riosmena, Kuhn, & Jochem, 2017 ). Though, research shows foreign-born Hispanics are more likely to engage in negative health behaviors such as smoking with increased duration in the United States which leads to the weakening of any immigrant health advantage ( Fenelon, 2013 ; Lariscy et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This contradiction between the relative socioeconomic disadvantage and health of Hispanics vis-a-vis whites has been labeled the Hispanic paradox ( Markides & Eschbach, 2011 ). Potential explanations for the observed health advantage among older Hispanics have been attributed to (a) selective migration: in-migration of healthy individuals and return migration of older Hispanics in poor health to their country of origin, which results in a healthier Hispanic population residing in the United States ( Bostean, 2013 ; Markides & Eschbach, 2005 ); and (b) social and cultural factors among Hispanic immigrants associated with positive health behaviors (e.g., lower levels of smoking, and healthier diet) that promote health and longevity ( Bostean, Ro, & Fleischer, 2017 ; Fenelon, 2013 ; Lariscy, Hummer, & Hayward, 2015 ; Riosmena, Kuhn, & Jochem, 2017 ). Though, research shows foreign-born Hispanics are more likely to engage in negative health behaviors such as smoking with increased duration in the United States which leads to the weakening of any immigrant health advantage ( Fenelon, 2013 ; Lariscy et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of immigrant arrival on smoking status has been evaluated using NHIS data and confirmed that Latino immigrants maintained lower rates of current smoking compared with US-born Latinos. 28 Furthermore, in that study, longer duration in the United States is associated with lower odds of smoking among men. Duration of residence in the United States has often been used as a proxy for acculturation and thus our findings are consistent.…”
Section: Discussionmentioning
confidence: 64%
“…11,22 However, none, to our knowledge, have investigated educational attainment or household income in this relationship by national background. Two recent articles used National Health Interview Survey (NHIS) data to evaluate smoking behavior 28 or smoking cessation 29 , but neither reported data by national background. In order to investigate the relationship between gender, acculturation level, educational attainment, and household Latinos have not been disaggregated by national background nor accounted for any measure of socioeconomic status such as years of formal education or household income.…”
Section: Acculturation and Smoking Behavior In Latinos -Rodriquez Et Almentioning
confidence: 99%
“…The consideration of a wide range of topics is needed to better inform decision makers and the medical community [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. This includes, but is not limited to: Health screening examinations; community-based/multi-lingual health education and resources for refugees; improved awareness of refugee health disparities; disease tracking and reporting systems; multidisciplinary response to disease outbreaks; refugee utilization or lack thereof of healthcare resources/insurance; barriers to healthcare; health selection/trajectory of refugees; hematologic genetic disorders; chronic and mental health issues; abuse; discrimination; exploitation; infectious diseases; immunization strategies; environmental exposures related to disease; hygiene and sanitation; healthy lifestyle choices; illegal activities/injuries (assault, rape, battery); and assimilation analysis.…”
Section: Moving Toward a Solutionmentioning
confidence: 99%